2019
DOI: 10.1002/jor.24555
|View full text |Cite
|
Sign up to set email alerts
|

Selective Agonists of Nuclear Retinoic Acid Receptor Gamma Inhibit Growth of HCS‐2/8 Chondrosarcoma Cells

Abstract: Chondrosarcoma is the second most common primary bone sarcoma. Treatment of chondrosarcoma is limited to surgery due to radiation and chemotherapy resistance of this cancer. An ideal treatment for chondrosarcoma would be a well-tolerated, minimally invasive local or systemic treatment modality to halt or slow tumor growth prior to resection of local, unresectable local, or metastatic disease. Palovarotene, an agonist of nuclear retinoic acid receptor γ (RARγ) has shown therapeutic action for treatment of heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…We selected the 7C compounds for this purpose because 7C stimulates the ectopic bone formation via systemic administration ( Uchibe et al, 2017 ) and has similar chemical properties in size, organophilicity and structure to those of NRX204647 ( Supplementary Figure S1 ). The NRX204647 loaded PLA-NPs successfully inhibit chondrosarcoma growth with minimum local tissue damage ( Shield et al, 2020 ). To examine the action of 7C-NPs on bone formation, 7C-NPs or blank-NPs were mixed into the BMP-2 pellets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We selected the 7C compounds for this purpose because 7C stimulates the ectopic bone formation via systemic administration ( Uchibe et al, 2017 ) and has similar chemical properties in size, organophilicity and structure to those of NRX204647 ( Supplementary Figure S1 ). The NRX204647 loaded PLA-NPs successfully inhibit chondrosarcoma growth with minimum local tissue damage ( Shield et al, 2020 ). To examine the action of 7C-NPs on bone formation, 7C-NPs or blank-NPs were mixed into the BMP-2 pellets.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, by applying the drug locally, we could minimize systemic side-effects. Furthermore, we recently formulated NRX204647-loaded PLA-NP which successfully inhibited chondrosarcoma growth with minimum local tissue damage ( Shield et al, 2020 ). Since the chemical properties of NRX204647 and 7C are quite similar in size, organophilicity, and structure ( Supplementary Figure S1 ), we predicted that PLA-NP is a suitable drug vehicle for our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that RAR γ plays an essential role in cartilage matrix and proteoglycan homeostasis [ 19 ]. RAR γ activation could exhibit an antitumor effect on chondrosarcomas through promoting cartilage matrix degradation, inhibiting matrix synthesis, and inducing cell death [ 20 , 21 ]. RAR γ could regulate the expression of specific genes in the differentiation of mice hypertrophic chondrocytes, such as Tg2, Mmp13, Col10A1, and Ccn2 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%